KOMUNITAS RAYAP TANAH PADA EMPAT LOKASI DI JAKARTA DAN JAWA BARAT - Ginuk Sumarni; Agus Ismanto (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
The community of subterranean termite in any site is influenced by the soil condition. In three places studied six species of termites were found namely Macrotermes gilvus (Hagen), Microtermes insperatus Kemner, M. incertoides Holmgren, Odontotermes grandiceps Holmgren, Capritermes buitenzorgi Holmgren and Coptotermes havilandi Holmgren.In the yard of National Oceanological Institute Jakarta C. havilandi was responsible for the damage of the building. In the yard of Forest Product Research and Development Centre in Bogar four species of termite were observed, while at Cibodas Botanical Garden only one species was found namely C. buitenzorgi. The latter termite did not seem to cause to the building.